The propagation paths of the Catholic doctrine of the Trinity in the Ming and Qing dynasties - He, Xianyue (HTS teologiese studies, 2024)
According to historical analysis and textual interpretation, the propagation of the Catholic doctrine of the Trinity in the Ming and Qing dynasties was closely related to Matteo Ricci. When entering China, Ricci put forward the ‘Theory of Buddhist-Daoist Plagiarism’, asserting that Buddhism and Taoism had plagiarised the Catholic doctrine on the triune God. As for Confucianism, he pointed out that the ancient Confucian classics did not contain the doctrine of the Trinity, which he attributed to various facters, leading to what may be termed the ‘Confucian Absence Theory’. Matteo Ricci’s interpretations and propositions regarding the Chinese Trinity paved the way for the ‘Yi-Fo School’, the ‘Bu-Ru School’ and the Figurism, which emerged during the dissemination of the Trinity in the Ming and Qing dynasties. The ‘Yi-Fo School’ advocated replacing the Buddhist Trinity with the Catholic Trinity to complement the perceived absence in Confucianism, thus forming the ‘Bu-Ru School’. In contrast, Figurism advocated for use of Chinese characters and texts as clues to uncover the missing Trinity in Confucian classics. Regarding Matteo Ricci’s viewpoints and the above three paths, Buddhism of that era believed that Catholicism had plagiarised the Buddhist doctrine of the Trinity, and modern Chinese scholars also argued that the views of the Figurism were overly far-fetched. These paths placed the Trinitarian doctrines of Catholicism, Buddhism and Daoism in a cross-linguistic and cross-cultural comparative framework, underscoring the methodological significance of exchanges and mutual learning among civilisations.Contribution: This article examines the nexus between Matteo Ricci and the propagation of the Catholic doctrine of the Trinity in the Ming and Qing dynasties. It also investigates the evolution of three distinct pathway for this doctrinal propagation and assesses the Chinese Populace’s reactions, as well as the interplay of their discourses.